Gut Microbiota and Intestinal Epithelial Myd88 Signaling Are Crucial for Renal Injury in UUO Mice - Watanabe, Ingrid Kazue Mizuno; Andrade-Silva, Magaiver; Foresto-Neto, Orestes; Felizardo, Raphael José Ferreira; Matheus, Marco Aurélio Costa; Silva, Reinaldo Correa; Cenedeze, Marcos Antônio; Honda, Tâmisa Seeko Bandeira; Perandini, Luiz Augusto Buoro; Volpini, Rildo Aparecido; Pacheco-Silva, Alvaro; Câmara, Niels Olsen Saraiva (Frontiers in Immunology, 2020)
Increasing evidence show the essential participation of gut microbiota in human health and diseases by shaping local and systemic immunity. Despite an accumulating body of studies showing that chronic kidney disease (CKD) is closely associated with disturbances in the composition of gut microbiota, it remains unclear the importance of gut microbiota in the onset and development of CKD. For the purpose of untangling the role of gut microbiota in CKD, gut microbiota was depleted with a pool of broad-spectrum antibiotics in mice submitted to unilateral ureteral obstruction (UUO). Depletion of gut microbiota significantly decreased levels of proinflammatory cytokines and fibrosis markers, attenuating renal injury. Additionally, to study whether the pathogenic role of gut microbiota is dependent of microbial-host crosstalk, we generated mice lacking Myd88 (myeloid differentiation primary response gene 8) expression in intestinal epithelial cells (IECs) and performed UUO. The absence of Myd88 in IECs prevented a bacterial burden in mesenteric lymph nodes as observed in WT mice after UUO and led to lower expression of proinflammatory cytokines and chemokines, reducing deposition of type I collagen and, ultimately, attenuating renal damage. Therefore, our results suggest that the presence of gut microbiota is crucial for the development of CKD and may be dependent of Myd88 signaling in IECs, which appears to be essential to maturation of immune cells intimately involved in aggravation of inflammatory scenarios.